Pharmaceutical Chemistry (analysis of drugs that affect the afferent nervous system and drugs that improve blood supply to organs and tissues, as well as antihistamines and sulfonamides). Section 2.2: Study guide for 3rd year English-speaking students of the specialty "Pharmacy, Industrial Pharmacy" - Kucherenko, L. I.; Portna, O. O.; Khromylova, O. V.; Nimenko, H. R.; Borsuk, S. O.; Кучеренко, Людмила Іванівна; Портна, Олена Олексіївна; Хромильова, Ольга Володимирівна; Німенко, Ганна Романівна; Борсук, Сергій Олександрович (Запорізький державний медичний університет, 2023)
The study guide for students is compiled in accordance with the requirements of the Central Methodical Council of Zaporizhzhia State Medical University. Published for the first time.